The Impact of Gadget Use and Mentoring Strategies for Elementary School Students: A Literature Review - Ni Made Yeni Suranti; Ni Ketut Yeni Pradmawati (Indonesian Journal of Elementary and Childhood Education, 2026)
The development of digital technology has led to the widespread use of gadgets in society, including among elementary school-aged students. Gadgets are used as easily accessible learning, communication, and entertainment tools for children. However, uncontrolled gadget use has the potential to have various negative impacts on child development. This article aims to examine the impact of gadget use on the development of elementary school-aged students and efforts to address these negative impacts. The research method used is a literature review, analyzing various scientific sources, including books, journal articles, and proceedings relevant to the topic. The results indicate that gadget use can affect children's cognitive, emotional, social, character, and physical development. Therefore, the active involvement of parents, schools, and the surrounding community is needed to monitor, limit, and direct gadget use so that it can be used wisely, healthily, and in a balanced manner, thus supporting the optimal growth and development of elementary school-aged students in their daily.